2006
DOI: 10.1007/s00586-006-0161-5
|View full text |Cite
|
Sign up to set email alerts
|

Thoracolumbar fractures surgically treated by “in situ contouring”

Abstract: This is a retrospective study on a series of 70 patients with thoracolumbar fractures (TL), surgically treated by the in situ bending technique (ISB). Its purpose is to show the performances and limits of the ISB technique for the early correction of post-traumatic spine deformities as well as to estimate the overall outcome in this series and to discuss the indications for anterior grafting. Although the management of limbs fractures is a cleared issue today, spine fractures management is still a matter of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
24
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 50 publications
4
24
0
2
Order By: Relevance
“…In contrast, the in situ rod-contouring technique can provide greater strength to directly correct the scoliosis rigid deformity. 17,18 As expected, our results indicated that a good correction ratio was obtained in the scoliosis Cobb angle in the coronal plane, from 85.7° (range 77°-94°) preoperatively to 33.1° (range 21°-52°) postoperatively.The in situ rod-contouring technique is not usually used because it may lead to bone fracture and neurologi- …”
supporting
confidence: 86%
“…In contrast, the in situ rod-contouring technique can provide greater strength to directly correct the scoliosis rigid deformity. 17,18 As expected, our results indicated that a good correction ratio was obtained in the scoliosis Cobb angle in the coronal plane, from 85.7° (range 77°-94°) preoperatively to 33.1° (range 21°-52°) postoperatively.The in situ rod-contouring technique is not usually used because it may lead to bone fracture and neurologi- …”
supporting
confidence: 86%
“…The parameters used for radiographic evaluation were the sagittal index of the fractured segment (Fracy's sagittal index [5]); the relation between the traumatic vertebra body height and the adjacent vertebrae (compression percentage = 100 -(2 · F/A + B) · 100. F-height of fractured vertebra, A-height of the proximal vertebra, B-height of the distal vertebra) [21]; the height of the intervertebral disk above and below the fractured vertebra; classification of the fracture based on load sharing according to McCormack et al [16]; loosening and rupture of the implants used for fixation.…”
Section: Methodsmentioning
confidence: 99%
“…The deformity is corrected by in situ contouring [3,4] and we believe that the optimum correction of the regional deformity is achieved by the posterior approach. The spinal stabilization by means of pedicle screws allows for a global approach of Louis's three-column spine [5].…”
Section: Introductionmentioning
confidence: 99%
“…The spinal stabilization by means of pedicle screws allows for a global approach of Louis's three-column spine [5]. Corporeal screws stabilize only the anterior column and therefore they are less efficient and the construct is less stable [4].…”
Section: Introductionmentioning
confidence: 99%